585 divacancy-defective germanene as a hydrogen separation membrane: A DFT study. (21st September 2017) - Chang, Xiao; Xue, Qingzhong; He, Daliang; Zhu, Lei; Li, Xiaofang; Tao, Baoshou
Abstract: As sustainable and clean energy, hydrogen is the most attractive and promising energy source in the future. Membrane separation is attractive due to its high hydrogen separation performance and low energy consumption. Van-der-Waals-corrected density functional theory (DFT) calculations are performed to investigate the hydrogen separation performance of 585 divacancy-defective germanene (585 germanene). It is found that the 585 germanene presents a surmountable energy barrier (0.34 eV) for hydrogen molecule passing through the membrane, and that membrane exhibits extremely high selectivity for H2 molecules over CO, CO2, N2, CH4 and H2 S molecules in a wide range of temperatures. Meanwhile, the hydrogen permeance of 585 germanene can reach 1.94 × 10 −7 mol s −1 m −2 Pa −1 at the low limit temperature of methane reforming (at 450 K), which is higher than the industrially acceptable gas permeance. With high selectivity and permeance, the 585 germanene is a promising candidate for hydrogen separation. Graphical abstract: Using van-der-Waals-corrected DFT calculations, we demonstrate that 585 divacancy-defective germanene has a good performance for H2 separation and it can serve as a superior membrane for H2 separation. Highlights: A new 585 divacancy-defective germanene is designed for H2 separation. The H2 separation performance of 585 germanene is studied using DFT calculations. The 585 germanene can exhibits excellent H2 separation performance.